The inhibitory effect of zoledronate on early-stage osteoinduction by recombinant human bone morphogenetic protein 2 in an osteoporosis model. (June 2015) - Lee, Jae Hyup; Baek, Hae-Ri; Lee, Kyung Mee; Zheng, Guang Bin; Shin, Sung Joon; Jin, Yuan Zhe
Abstract This study evaluated the effect of the combined treatment of intravenous zoledronic acid (ZA, 0.08 mg/kg) and rhBMP-2 (5 µg) on osteogenesis in a calvarial defect model of ovariectomized SD rats. New bone formation was evaluated 4 or 8 weeks after calvarial defect implantation using micro-CT and histology. Micro-CT results revealed that the rhBMP-2 group showed significantly higher calvarial defect coverage ratio compared with the ZA + rhBMP-2 group at 4 weeks. In addition, bone formation indices were significantly lower in ZA + rhBMP-2 group when compared with the rhBMP-2 group after 4 weeks, which indicates a negative effect of ZA on the initial bone formation and the bone quality. At 8 weeks, the negative effect induced by ZA treatment was alleviated as time passed. Histological examination showed similar results to the micro-CT measurements. In conclusion, although ZA treatment lowered the new bone formation induced by rhBMP-2 initially, as time passed, the negative effect was decreased.